2018
DOI: 10.1123/japa.2017-0270
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Relation to Sleep Among Community-Dwelling Older Adults in China

Abstract: This cross-sectional study was conducted to describe the physical activity and sleep in 290 community-dwelling Chinese older adults and to examine the association between physical activity and poor sleep outcomes. Almost half of the samples were poor sleepers. The majority of the samples regularly participated in walking, some household activity, and light sports, yet only a small portion were involved in work-related activity or in strenuous sports. A greater level of overall physical activity (odds ratio = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 36 publications
(48 reference statements)
6
14
0
Order By: Relevance
“…Finally, our second hypothesis stated that good sleep quality would be associated with sufficient PA in the elderly. The results of our study confirmed this hypothesis and are in line with previous studies conducted among the same population [ 13 , 30 , 31 ]. Specifically, two cross-sectional studies [ 30 , 31 ] have shown that good subjective sleep quality was positively associated with PA.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, our second hypothesis stated that good sleep quality would be associated with sufficient PA in the elderly. The results of our study confirmed this hypothesis and are in line with previous studies conducted among the same population [ 13 , 30 , 31 ]. Specifically, two cross-sectional studies [ 30 , 31 ] have shown that good subjective sleep quality was positively associated with PA.…”
Section: Discussionsupporting
confidence: 93%
“…The results of our study confirmed this hypothesis and are in line with previous studies conducted among the same population [ 13 , 30 , 31 ]. Specifically, two cross-sectional studies [ 30 , 31 ] have shown that good subjective sleep quality was positively associated with PA. Moreover, a longitudinal study by Holfeld and Ruthig [ 13 ] showed that better initial sleep quality predicted higher levels of later PA, yet initial PA did not predict later sleep quality.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the mean sleep period duration (ie, interval between bedtime and wake‐up time) was 7.7 h/d; given that the sleep efficacy was of 85.9%—with a WASO around 1.1 h/d, and the mean sleep time was 6.6 h/d. These results are similar to those of previous studies using accelerometry in older people, in which the sleep duration ranged from 6.3 to 6.6 h/d . As in previous research, no marked differences were generally observed in sleep patterns by socio‐demographic factors and BMI; however, women showed greater sleep time and sleep efficiency than men, who accumulated more WASO time.…”
Section: Discussionsupporting
confidence: 90%
“…These results are similar to those of previous studies using accelerometry in older people, in which the sleep duration ranged from 6.3 to 6.6 h/d. 4,5,25,26 As in previous research, 10 no marked differences were generally observed in sleep patterns by socio-demographic factors and BMI; however, women showed greater sleep time and sleep efficiency than men, who accumulated more WASO time. Moreover, participants with obesity showed lower sleep efficiency and were less likely to meet the sleep recommendations.…”
Section: Discussionsupporting
confidence: 63%
“…Sleep disturbances are common features in older adults, such as sleepiness at daytime, fractionated sleep at night (117)(118)(119), among others. It has been shown in the elderly, both men and women, that low to moderate physical activity improved sleep quality (120)(121)(122)(123)(124)(125)(126)(127)(128)(129)(130)(131)(132)(133). In animals, sleep derangement related to the aging process also happens (134,135).…”
Section: Physical Exercise and Agingmentioning
confidence: 99%